ISOLASI DAN IDENTIFIKASI BAKTERI LIMBAH BIODIESEL PENGHASIL BIO-ENERGI DAN BIO-MATERIAL - Rachman, Mahyudin Abdul (BPPT)
Glycerol from the waste of biodiesel can be utilized to 1,3-propanediol (PDO) and hydrogen gas (H2) with biotransformation processing. The product of PDO will be used as raw material for polymer, polyurethane and polyester and H2 will be converted to electrical energy by using Fuel-cell. The anaerobe or aerobe bacterium which has ability to degrade biodiesel waste for environmental friendly such as genus Enterobacter, Klebsiella, Clostridium, Bacillus, Citrobacter, etc. The direct screening of bacteria for isolation from biodiesel waste in order to obtain the bacteria which has highest conversion of glycerol to PDO and H2. We have found that 28 species from liquid and 7 from solid biodiesel waste and by using IMVIC testing, 7 species of bacteria was Klebsiella or Enterobacter which can be predicted to convert glycerol for PDO and H2. The highest yield product was species TH3from biodiesel waste. Moreover, the microbiology identification indicated that the strain TH3 was Klebsiella sp. strain 23 with 98 % similarity.Key words : Waste of biodiesel, Glycerol, PDO, H2and bacteria.